Global Economic Prospects : Commodity Markets Outlook, January 2014 - Baffes, John; Cosic, Damir (World Bank, Washington, DC, 2014)
With the exception of energy, all the key commodity price indices declined significantly in 2013. Fertilizer prices led the decline, down 17.4 percent from 2012, followed by precious metals (down almost 17 percent), agriculture (-7.2 percent), and metals (-5.5 percent). Crude oil prices (World Bank average), which have been remarkably stable during the past three years, averaged $104/barrel (bbl) during 2013, marginally lower than the $105/bbl average of 2012. Most non-energy commodity prices, notably grains, followed a downward path during 2013. Other risks for agricultural markets are mostly on the downside as well. For example, the risk of trade policies impacting agricultural prices is low as evidenced by the absence of any export restrictions during 2011-13, despite several spikes in prices (notably maize and wheat). Finally, production of biofuels experienced a third year of little (or no) growth, as policy makers increasingly realize that the environmental and energy independence benefits from biofuels may not outweigh the costs.